Performance of The Bandungan District Chrysanthemum Supply Chain Management - Adityo Azana Putra; Masyhuri Masyhuri; Jamhari Jamhari (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2019)
Chrysanthemums are included in a group of flowers with relatively high economic value. The demand for chrysanthemums increases from year to year so that special concern for chrysanthemums is required in order that their quality and availability are maintained. Bandungan as one of the centers of chrysanthemum production in Indonesia has some problems in functioning as part of the chrysanthemum supply chain, such as, 1) difference in selling price based on time of day, 2) difference in selling price based on days of importance, and 3) there still being a long supply chain to go through. The research concerned here aimed at measuring the performance of chrysanthemum supply chain management in Bandungan by using the SCOR analysis with five performance attributes, namely, 1) supply chain reliability, 2) supply chain responsiveness, 3) supply chain agility, 4) supply chain cost, and 5) supply chain asset management. The research was conducted in February 2019. The research was descriptive type with quantitative approach. The sample consisted of farmer, retailer, florist and consumer which numbered 30 respondents. The result shows that the perfomance in relation with supply chain reliability, supply chain responsiveness, and supply chain agility is satisfactory in category (with scores within the 31-40 range) while the performance in relation with supply chain cost and supply chain asset management is moderate in category (with scores within the 21-30 range). The performance of chrysanthemum supply chain management in Bandungan would become increasingly better if all the actors in the supply chain take special notice of any performance that is done. The result of the research could hopefully be a reference in the making of strategies for development and improvement in the chrysanthemum business in Bandungan.